AB0052 Progressive symmetric arthritis as an early manifestation of adeno carcinoma of the lung. (1st June 2001) - Welcker, M; Hobert, H; Welcker, K; Kaufmann, D; Franck, H
Abstract : Background: In may 1999 a 57 year old woman presented progressive symmetric arthritis of the hand, fingers and forefoot over a period of more than 6 weeks. Laboratory testing revealed an elevated sedimentation rate, increased C reactive protein levels and secondary signs of inflammation (elevated ferritine, alpha-2-fraction in the serum electrophoreses, etc.). The radiograph showed juxtaarticular osteoporosis without further signs of joint destruction. The x-ray of the chest was normal (performed for reasons of nicotin consumption over years and the intention of methotrexate therapy) without signs of malignancy. Initially the patient was treated as an outpatient. Although the initiated DMARD-therapy with methotrexate was well tolerated at a dose of 15 mg orally per week she was finally admitted to the hospital in December 1999 for reasons of further deteriorating of the arthritis and the general feeling. Symmetrical arthritis and elevated sedimentation rate revealed continuous inflammation. An x-ray control of the hand and feet showed a fine periostal hyperostosis suspective for "osteoarthropathy hypertrophiante pneumonique Pierre Marie Bamberger". The x-ray of the chest was suspective for a malignant process of the lung, a diagnose that was confirmed by computer tomography. Histological examination revealed an adeno carcinoma of the lung. Consecutive palliative chemotherapy led to improvement of arthritis. Objectives: ./. Methods: ./. Results: ./. Conclusion: This is a case of malignant lung disease with the rare initial symptom of symmetric progressive arthritis and periostal hyperostosis, improving after chemotherapy.